Complete First Certificate: Workbook with answers - Thomas B. Barbara (Cambridge, Cambridge University Press, 2010)
Complete First Certificate is a brand new course for the revised First Certificate exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at teenagers and young adults. The course covers every part of the First Certificate exam in detail providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by the Cambridge Learner Corpus and providing a complete First Certificate exam paper specially prepared by Cambridge ESOL, Complete First Certificate is the most authentic exam preparation course available. Complete First Certificate Student's Book with answers: contains 16 topic-based units. Each unit covers one part of each First Certificate paper is informed by the Cambridge Learner Corpus to help students tackle typical First Certificate problem areas includes a complete model exam paper supplied by Cambridge ESOL includes a CD-ROM for self-study provides Writing and Speaking reference sections dedicated to the Writing and Speaking papers contains a comprehensive Grammar reference section contains an answer key and recording scripts. Complete First Certificate Workbook with answers: contains an answer key and recording scripts. includes 16 topic-based units providing additional exam-style practice includes a CD with workbook audio includes answer key and recording scripts.